2021
DOI: 10.3390/microorganisms9020337
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Production of Volatile Fatty Acids from Corn Stover Using Bioaugmentation of a Mixed Rumen Culture with Homoacetogenic Bacteria

Abstract: Volatile fatty acids (VFA) are industrially versatile chemicals and have a major market. Although currently produced from petrochemicals, chemical industries are moving towards more bio-based VFA produced from abundant, cheap and renewable sources such as lignocellulosic biomass. In this study, we examined the effect of bioaugmentation with homoacetogenic bacteria for increasing VFA production in lignocellulose fermentation process. The central hypothesis of this study was that inhibition of methanogenesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…For example, Kakar et al [38] reported a VFA yield of 1.53 g/g VS added during the AD of hydrothermally treated source separate organics. In another study, Murali et al [41] reported a total VFA yield of around 2.19 g/g VS during the anaerobic digestion of wet exploded corn stover while methanogenesis was inhibited using BES. There could be two possible reasons for high specific VFA yield in the case of torrefaction condensate.…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kakar et al [38] reported a VFA yield of 1.53 g/g VS added during the AD of hydrothermally treated source separate organics. In another study, Murali et al [41] reported a total VFA yield of around 2.19 g/g VS during the anaerobic digestion of wet exploded corn stover while methanogenesis was inhibited using BES. There could be two possible reasons for high specific VFA yield in the case of torrefaction condensate.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Hydrothermally treated thickened waste-activated sludge 1.53 [38] Glucose (methanogenesis inhibition using H 2 O 2 ) 1.23 [39] Food waste (methanogenesis inhibition using 2-bromoethanesulfonate) 0.8 [40] Pretreated corn stover (methanogenesis inhibition using 2-bromoethanesulfonate) 2.19 [41] Pulp sludge torrefaction condensate (methanogenesis inhibition using 2-bromoethanesulfonate) 1.1-4.78 This study…”
Section: Substratementioning
confidence: 99%
“…For the extraction of propionic acid, trioctylamine was used in supercritical CO 2 , high extraction productivity was achieved (97%-propionic acid), only a small portion vanished acid-amine complex formation. Pressure and temperature conditions need to be maintained as they have a high effect on productivity [213][214][215].…”
Section: Process Of Reactive Extractionmentioning
confidence: 99%
“…It might offer a pathway to address two pressing challenges of the current times: agricultural productivity and climate change mitigation. Studies have been performed on the effect of microbial bioaugmentation in rumen cultures, particularly in vitro in semi-continuous bioreactor setups, where improvements in the productivity of acetic acid and other VFAs were observed [22]. The effects of bioaugmentation were promising, with a substantial increase in acetic acid productivity concurrent with a low hydrogen concentration in the headspace [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Among the array of biochar variants that hold economic appeal for integration into livestock feed additives in the USA is almond shell biochar, a waste from almond production. Almond shells and hulls are already today employed within the dairy industry as bedding and feed additives, respectively [22].…”
Section: Introductionmentioning
confidence: 99%